The mediating role of adoption of an electronic tax system in the relationship between attitude towards electronic tax system and tax compliance - Night, Sadress (2020)
Purpose: The purpose of this paper is to examine the mediating effect of adoption of electronic tax system in the relationship between attitude towards electronic tax system and tax compliance using evidence fromsmall business enterprises (SBEs) of an African developing economy. Design/methodology/approach – This study used a quantitative research approach where questionnaires with close-ended questions were used. This study’s research design was cross-sectional and correlational. Usable questionnaires were received from 214 managers of SBEs and data were analysed with the help of SPSS v22 and MedGraph program (Excel version). Findings – Adoption of electronic tax system is a partial mediator in the association between attitude towards electronic tax system and tax compliance. Results further indicate that adoption of electronic taxsystemand attitude towards electronic tax system are significantly associated with tax compliance. Research limitations/implications – This study was cross-sectional and monitoring changes in behaviour over time was not possible. The study used a quantitative research approach and this limits respondents from expressing their feelings fully. The study was conducted in Uganda and it is possible that the results of this study can be generalized to developing countries with environments similar to that of Uganda.Originality/value – Whereas there has been a number of studies on tax compliance this study provides an initial empirical evidence on the mediation effect of adoption of electronic tax system in the relationshipbetween attitude towards electronic tax system and tax compliance using evidence from SBEs of an African developing economy – Uganda.